2007
DOI: 10.1021/ja073886g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Generation from Weak Acids:  Electrochemical and Computational Studies of a Diiron Hydrogenase Mimic

Abstract: Extended investigation of electrocatalytic generation of dihydrogen using [(mu-1,2-benzenedithiolato)][Fe(CO)3]2 has revealed that weak acids, such as acetic acid, can be used. The catalytic reduction producing dihydrogen occurs at approximately -2 V for several carboxylic acids and phenols resulting in overpotentials of only -0.44 to -0.71 V depending on the weak acid used. This unusual catalytic reduction occurs at a potential at which the starting material, in the absence of a proton source, does not show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
392
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(438 citation statements)
references
References 56 publications
35
392
0
1
Order By: Relevance
“…Diiron-dithiolate compounds of the type [Fe 2 (µ-SRS)(CO) 6-x L x ] (R = organic group, L = electron-donor ligand, x ≤ 4) have been shown to electrocatalyze the reduction of acid in organic solvents [19][20][21] and, very recently, in aqueous micellar solutions [22,23](for examples of photo-driven H 2 -production by diiron-dithiolate compounds see [24,25]). The electrocatalytic pathway entails successive electron and proton transfers in a sequence that depends on the nature of the terminal ligand L and the strength of the acid used as proton source [16,26] We [27][28][29][30][31][32], and others [33][34][35][36][37] [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diiron-dithiolate compounds of the type [Fe 2 (µ-SRS)(CO) 6-x L x ] (R = organic group, L = electron-donor ligand, x ≤ 4) have been shown to electrocatalyze the reduction of acid in organic solvents [19][20][21] and, very recently, in aqueous micellar solutions [22,23](for examples of photo-driven H 2 -production by diiron-dithiolate compounds see [24,25]). The electrocatalytic pathway entails successive electron and proton transfers in a sequence that depends on the nature of the terminal ligand L and the strength of the acid used as proton source [16,26] We [27][28][29][30][31][32], and others [33][34][35][36][37] [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The two-electron one-proton intermediate 1H − must hence be further reduced to produce H 2 at an appreciable rate, but with a large thermodynamic cost of about 0.8 V [33]. In an attempt to obtain diiron-dithiolate electrocatalysts achieving balanced basicity and reduction potential, we focused on the mono-substituted derivative [Fe 2 (µ-bdt)(CO) 5 (P(OMe) 3 )] (2, Scheme 1) [29].…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that immobilized 1 on CB via DDAB liposomes underwent a quasi-reversible electrochemical process. CVs collected in Na 2 SO 4(aq) solution showed a redox 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 behavior similar to that in CH 3 CN solution [14] (Figure S7), and thus the reduction wave in aqueous solution was assigned to a two-electron reduction process.…”
mentioning
confidence: 65%
“…The large deviation of a from 0.5 implies the force constants for the reactant and the product are unequal (according to the asymmetric Marcus theory), [16] which is in agreement with substantial structural changes upon reduction of 1 to 1 2À . [14] The apparent heterogeneous electron transfer rate constant (k s ) was calculated to be 1.33 AE 0.15 s À1 (see Supporting Information). The k s of 1@DDAB/CB was comparable with values of a range of electrodes modified with electroactive species in literature (Table S2).…”
mentioning
confidence: 99%
“…At acid concentrations above 0.4 M, the current is acidindependent indicating the solution is acid saturated, and that CV response is no longer limited by diffusion (Figure 12;inset). 121,[163][164][165] Under these pseudo-first order conditions, the turnover frequency (TOF), which is also the observed rate constant, is 30 ± 4 s -1 .…”
Section: Culmentioning
confidence: 82%